Displacement in Architecture An analytical study in contemporary mosques design - Parizat Qassim Alâ€Salhi; Nada khteer Alâ€Nouaimi; Anwar Subhi Ramdan Al-Qaraghuli (Iraqi Journal of Architecture and Planning, 2009)
Previous architectural studies have presented new concems for contemporarydesign of mosques. These concems were raised on both academic and professionallevels. what is significant is to elaborate on special aspects of these concems, instead of limited understanding without it being comprehensive enough to utilizc the mentaland intellectual content in the local meliue.Displacement represents a major concern specially its relationship to conceptsand forms; and what the design process aims at to achieve uniqueness in expression. It is possible to enterprite unique qualities in ideas expressed architecturally as adisplacement of current types, which is founded on a deep design problem.This paper discusses displacement with the abore rtat"d context, aiming toachieve. a contemporary frame work theory a discussion of current theories Ind application to achieve a distinguish mosque aichitecture.